Measuring performance heterogeneity within groups: A two-dimensional approach - Michael Fritsch; Andreas Stephan (Technische Universität Bergakademie Freiberg, Fakultät für Wirtschaftswissenschaften, 2004)
We introduce a new two-dimensional measure for the heterogeneity of performance within groups of economic units. This measure accounts both, for the relative performance of the single units of groups and their relative size. We demonstrate that the new measure leads to a much more differentiated description of heterogeneity than alternative measures, for example, the mean or range. In particular, we provide an example to demonstrate that the proposed measure of heterogeneity is relatively robust with regard to extreme values of units ("outliers") with a relatively small size. – – Wir stellen ein neues zweidimensionales Maß für die Heterogenität der Leis-tungsfähigkeit innerhalb von Gruppen ökonomischer Einheiten vor. Dieses Maß berücksichtigt neben der Leistungsfähigkeit auch die relative Größe der betreffen-den Einheiten. Wir zeigen, dass dieses neue Maß die Heterogenität innerhalb von Gruppen wesentlich differenzierter beschreibt als alternative Maße, wie etwa das arithmetische Mittel und die Spannweite. Anhand eines numerischen Beispiels kann gezeigt werden, dass unser Maß vergleichsweise robust gegenüber extremen Werten ('Ausreißern') relativ kleiner Einheiten ist.
Keywords: C10; C43; L25; 330; Performance; heterogeneity; dispersion measures; Leistungsfähigkeit; Heterogenität; Streuungsmaße